2013
DOI: 10.1194/jlr.m027060
|View full text |Cite
|
Sign up to set email alerts
|

Cell wounding activates phospholipase D in primary mouse keratinocytes

Abstract: Journal of Lipid Research Volume 54, 2013 581characterized by growth arrest and expression of the mature keratins 1 and 10 in the fi rst differentiated layer of the epidermis, the spinous layer. Early differentiation in the spinous layer is followed by further differentiation in the granular layer, which is accompanied by expression of proteins that are essential for the formation of the cornifi ed envelope and corneocytes. The corneocytes constitute the outer layer of the epidermis, the stratum corneum, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Furthermore, knock-out mice with a nonsense mutation in PLD4 manifest a phenotype with thin hair and growth retardation [28]. In addition, Arun et al [29] demonstrated the importance of phospholipase family D members in mediating the repair of plasma membrane disruptions in mice keratinocytes emphasising the role of these phospholipid signalling enzymes in membrane function and wound healing. A mutation in a phospholipase-domain containing protein ( PNPLA1 ) results in a severe cornification disorder in dogs, providing evidence for a key role of lipases in the keratinisation process and the metabolism of the epidermal barrier in general [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knock-out mice with a nonsense mutation in PLD4 manifest a phenotype with thin hair and growth retardation [28]. In addition, Arun et al [29] demonstrated the importance of phospholipase family D members in mediating the repair of plasma membrane disruptions in mice keratinocytes emphasising the role of these phospholipid signalling enzymes in membrane function and wound healing. A mutation in a phospholipase-domain containing protein ( PNPLA1 ) results in a severe cornification disorder in dogs, providing evidence for a key role of lipases in the keratinisation process and the metabolism of the epidermal barrier in general [30].…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in the scheme presented in Fig 1A and 1B, micro-osmotic pumps were aseptically filled with either the vehicle (50% DMSO) or inhibitory compound at a concentration that would deliver 1.8 mg/kg/day of the PLD-specific inhibitors 5-fluoro-2-indolyl des-chlorohalopemide (FIPI) and N-[2-(4-oxo-1-phenyl-1,3,8-triazaspiro[4,5]dec-8-yl)ethyl]-2-naphthalenecarboxamide (VU0155072-2) ([VU0155072-2 has also been referred to as “NOPT” [31,4042]]; at a rate of 0.11 μl/hr for 45 days (Fig 1A and 1B). There are no cytotoxic effects of 750 nM or 7.5 μM FIPI or 1 μM VU0155072-2 on DNA or protein synthesis of keratinocytes in vitro [44]. …”
Section: Resultsmentioning
confidence: 99%
“…The authors proposed that the apparent diminished PG production was due to the disruption of the functional interaction of PLD2 with aquaporin-3 [67], or a previous PGdeficiency in the wounded cells. While exogenous glycerol [68] and PG [66] were shown to be able to rescue the delayed wound healing phenotype of aquaporin-3 KO mice [69], the role of PG and PLD2 in wound healing could also be linked to other PLD-derived lipids such as PA and DAG. This would be particularly interesting as it would be compatible with the DAG-rich zone observed by Vaughan et al [61].…”
Section: Dynamic Changes Of the Plasmalemma As Damage Signalsmentioning
confidence: 94%
“…production [66]. The authors proposed that the apparent diminished PG production was due to the disruption of the functional interaction of PLD2 with aquaporin-3 [67], or a previous PGdeficiency in the wounded cells.…”
Section: Dynamic Changes Of the Plasmalemma As Damage Signalsmentioning
confidence: 98%